Pendampingan Perencanaan dan Pelaksanaan Program Perilaku Hidup Bersih Dan Sehat (PHBS) Tatanan Rumah Tangga di Kelurahan Jambidan - Dwi Widiyanigsih (Humanism: Journal of Community Empowerment (HJCE), 2019)
ABSTRACTPHBS (Clean and Healthy Living Behavior) in household structure becomes very important because all aspects of health start from a healthy family. However the implementation of Clean and Healthy Living Behavior has not become a habit of the community, in this case Jambidan district. Therefore the incidence of diarrhea in infants continues. The environment unsanitary conditions are also still found in some residential areas, including household waste disposal as a significant obstacle which often causes unpleasant odors, and there are still many problems related to PHBS requiring assistance and involvement of all aspects of the community. Whereas for indirect causes there is a lack of mothers who exclusively breastfeed, so that many babies are susceptible to infectious diseases such as Diarrhea and ISPA (Acute Respiratory Infection). Unhealthy behaviors which currently become a trend in people's lifestyle are including smoking, lack of physical activity, and lack of consuming fruits and vegetables.With the assistance in planning and implementing the PHBS program in household structure, it has increased knowledge and awareness of the implementation of PHBS as evidenced by the success implementation of several programs of cleaning village, husbands’ support for exclusive breastfeeding and waste management from the source of the waste to ASRI village corner program. It can be said that the service programs are successful in general.Keywords: PHBS, household